DEVELOPMENT OF ETHNOLOGICAL SCIENCE IN KYRGYZSTAN (IN THE FIRST HALF OF THE 20TH CENTURY) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the Kyrgyz Republic, its the history and development prospects of the scientific ethnographic school for studying the culture of the Kyrgyz, both traditional and modern, from the standpoint of Russian ethnographic schools of science and partly socialist orientalist discourses. Despite the fact that the Turkic-speaking nomads of Eurasia “represent the external boundaries of the ‘East’ from the point of view of Orientalism,” let us try to fit the history of the study of the Kyrgyz Republic into the general context of Orientalist science.